2019
DOI: 10.1364/oe.27.030225
|View full text |Cite
|
Sign up to set email alerts
|

Experimental demonstration of tunable graphene-polaritonic hyperbolic metamaterial

Abstract: Tuning the macroscopic dielectric response on demand holds potential for actively tunable metaphotonics and optical devices. In recent years, graphene has been extensively investigated as a tunable element in nanophotonics. Significant theoretical work has been devoted on the tuning the hyperbolic properties of graphene/dielectric heterostructures, however, until now, such a motif has not been demonstrated experimentally. Here we focus on a graphene/polaritonic dielectric metamaterial, with strong optical reso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 49 publications
(52 reference statements)
0
18
0
Order By: Relevance
“…The metasurfaces with HMMs have been utilized for the asymmetric transmission [103] and high-efficiency wave-front manipulation [104]. The research scope of HMMs also has been extended to the actively controlled structures with graphene and VO2 [105][106][107], in which the hyperbolic dispersion and the associated properties can be actively tuned by changing the external field. In addition, many interesting phenomena and properties have been discovered in active HMMs, including the enhanced nonlinear effect [108][109][110], enhanced magnetooptical effect [111][112][113][114] and topological edge states [115,116].…”
Section: Introductionmentioning
confidence: 99%
“…The metasurfaces with HMMs have been utilized for the asymmetric transmission [103] and high-efficiency wave-front manipulation [104]. The research scope of HMMs also has been extended to the actively controlled structures with graphene and VO2 [105][106][107], in which the hyperbolic dispersion and the associated properties can be actively tuned by changing the external field. In addition, many interesting phenomena and properties have been discovered in active HMMs, including the enhanced nonlinear effect [108][109][110], enhanced magnetooptical effect [111][112][113][114] and topological edge states [115,116].…”
Section: Introductionmentioning
confidence: 99%
“…However, the feasibility of the proposed structure was considered in the analysis. In particular, similar graphene-based multilayer stacks have been experimentally demonstrated [ 31 , 42 ]. Additionally, the deposition process of active material deposition, e.g., Er-doped glass, may be realized by means of a compatible technology, e.g., RF magnetron sputtering [ 38 , 43 ].…”
Section: Theorymentioning
confidence: 99%
“…This class of structure, typically realized in the simple multilayer form, reveals unique dispersion properties that allow the obtaining of many practical functionalities, such as tunable spectral filters [ 11 ], perfect absorbers [ 12 ], and many others [ 13 , 14 , 15 , 16 , 17 , 18 ]. Since the pioneering work of Narimanov published in 2014 [ 10 ], the topic of photonic hypercrystals (PHCs) has been investigated both theoretically [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ] and experimentally [ 31 ]. It has been demonstrated that surface waves in a hypercrystal combine properties of Tamm states in the photonic crystal and surface plasmon polaritons at the metal–dielectric interface [ 10 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is because the other properties are more critical in other applications in being applied as terminal connectors, and such applications are beyond the scope of this work. Furthermore, the use of graphene as a tunable element has been investigated extensively in nanophotonics, indicating potential in providing a good range of tunability via the control of doping level by an external bias 28 …”
Section: Introductionmentioning
confidence: 99%